Experimental Investigations on Mechanical Properties of AZ31/Eggshell Particle-Based Magnesium Composites. (30th January 2022) - Ramanujam, N.; Muthukumaran, S.; Nagesawara Rao, B.; Ramarao, M.; Mangrulkar, Amol L.; Ashraff Ali, K. S.; Pugazhendhi, L.; Markos, Mebratu
Abstract : Magnesium (AZ31) is an excellent choice for a bionic implant. To enhance biocompatibility, the hardest graphene nanoparticles were reinforced with biocompatible materials. In this paper, biocompatibility composite material is produced by stir-casting nanoshell particles reinforced with various weight percentages (0, 1, 2, 3, and 4 wt. percent) of AZ31 magnesium alloy. To understand the mechanical properties of the composite material, results of which are compared to the base alloy (AZ31) are used. The study mentioned how AZ31 magnesium alloy, reinforced with reinforcing particles, may be used to create implant-related human bone materials. Magnesium alloy reinforced with reinforcing particles is described in the study.